Personal Data Protection and the Empowerment of Civil Liberty, Justice and Security: Universal Value of Globalization - Jashari, Ruzhdi (European Journal of Multidisciplinary Studies, 2016)
Protection of personal data and the privacy, at the time of final approval of the New Regulation on the protection of personal data, for the subjects of personal data brings hope; however, it is to believe that "in a world with protected privacy." Despite the challenge of protection of personal data in the era of colossal development of communication technology, the Internet and the major inventions of smart portable mobile devices, some new legal provisions are put in the Regulation of the EC, EU and the Parliament, in the future strengthens the protection of personal data; Freedom, justice and security, as notions that are spread in our country Kosovo, are the constitutional and legal obligations to provide stability to the country. However, the institutional strengthening of the law in this regard, with compact action (interaction) between the competent authorities within the country, our region and the competent authorities of the segment of rights and freedoms, justice and security of the EU, the EC and the European Parliament will undoubtedly bring success in the overcoming of challenges, through which the personal protection of data is going through. Strengthening of the National Authorities of personal data protection and freedom of information, is, and remains, the main input of justice, freedoms and security, now as standard globalist values.
Keywords: Protection of personal data, human rights, civil liberties and security